Sisi Gelap IKM Sapu Glagah Purbalingga: Strategi Pemanfaatan Kemampuan Inovasi Terhadap Keunggulan Bersaing - Humairo, Calista; Nurhayati, Eni Candra; Efendi, Bahtiar (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research investigates Strategieses to enhance the deployment of innovative capabilities through the dimensions of product innovation, process innovation, and service innovation on of competitive advantage in the Small and Medium Industries (SMIs) Glagah Brooms, Purbalingga Regency. The appropriate strategies for this investigation is a quantitative descriptive, which emphasizes the collection and analysis of data distributed to 106 respondents, all of whom are proprietors of the Small and Medium Industries (SMIs) in Glagah Brooms, Purbalingga Regency. The data were subjected to analysis multiple linear regression techniques and were processed utilizing IBM SPSS version 25.0 The results of this research show that: 1) Product innovation has no effect on competitive advantage. 2) The innovation process has a positive and significant effect on competitive advantage. 3) Service innovation has a positive and significant effect on competitive advantage